In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty–and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Papers of the "Forth Hill Conference on Southern Culture", held at Clemson Univ. (1989). Textes de Fort Hill Conference on Southern Culture, tenue à Clemson University au printemps de 1989.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)

Histoire des femmes en Occident - Duby, Georges; Perrot, Michelle (Plon, 1991)
Projet démesuré que de couvrir près de vingt siècles d'histoire du monde antique gréco-romain, de parcourir un espace qui va des rivages de la Méditerranée à ceux des mers du Nord, des colonnes d'Héraklès aux rives de l'Indus, de se plonger dans des documents aussi divers que les tombes d'une nécropole, la stèle inscrite plaquée aux murs du sanctuaire, le rouleau de papyrus, la scène peinte sur la panse d'un vase... et une littérature grecque et latine qui, si elle n'a pas donné la parole aux femmes, a beaucoup parlé d'elles. On l'aura deviné, ce livre n'a pas pour fonction de remplacer l'énorme production qui existe en ce domaine. Il aborde un petit nombre seulement des questions qui nous ont paru importantes pour aider à comprendre la place des femmes dans le monde antique et, plus encore peut-être, dans la perspective d'un ensemble de volumes traitant de l'histoire des femmes, comprendre les fondements d'habitudes mentales, de mesures juridiques, d'institutions sociales qui ont duré des siècles en Occident.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; antiquité; approches et analyses; conditions des femmes*; cours; discipline; europe; his4330; histoire; histoire des femmes*; histoire et politique; incontournable; lit3220; moyen-âge; occident; oui; outils; ouvrages de références; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Idola Saint-Jean et le radicalisme féministe de l’entre-deux-guerres - Lamoureux, Diane (Recherches féministes, 1991)
Les suffragistes nous semblent souvent de bonnes bourgeoises aux méthodes et aux idées surannées. Pourtant, le féminisme de l'entre-deux-guerres est aussi diversifié que le féminisme actuel. Il est utile d'analyser ce passé féministe dans le contexte du mouvement de réforme sociale de l'époque pour ensuite apprécier le radicalisme de la pensée politique d'Idola Saint-Jean, une pensée politique marquée au coin de la justice sociale, de la démocratie et d'un sens aigu de l'antagonisme entre les sexes qui conditionne son activité militante
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; amériques; approches et analyses; canada; cours; discipline; droit de vote; droits des femmes*; histoire et politique; justice sociale; pol4102; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; science politique; science politique et droit; suffragettes; thématiques